Re-organizing the Functional Bodies of the District-level People’s Committee and Downsizing the Civil Service - Giang, Pham Thi (VNU Journal of Science: Legal Studies; Vol 35 No 2DO - 10.25073/2588-1167/vnuls.4222, 2019)
The article focuses on streamlining the organizational structure of the functional bodies of the district-level People's Committee for more effective management. This is the basis for downsizing the civil service by screening the current civil servants with the purpose of replacing no longer suitable staff with competent servants to work in the functional bodies of the district-level People's Committee. In fact, although the state administrative reform since 2001 has helped reduce the number of the functional bodies under the district-level People's Committee from 15 agencies to 12 agencies, the number of civil servants in these agencies has increased. Therefore, the article offers a number of solutions for rationally downsizing the civil service. Keywords: Reorganization, functional body, payroll streamlining, district-level People's Committee. References: [1] Xem Dự thảo Nghị định ngày 10/4/2018 - Bộ Nội vụ, Quy định tổ chức các cơ quan chuyên môn thuộc UBND huyện, quận, thị xã, thành phố thuộc tỉnh, thành phố trực thuộc Trung ương. https://www.moha.gov.vn. [2] Nguyễn Văn Lượng, Đề tài khoa học cấp bộ “Nghiên cứu cơ sở khoa học xác định vị trí việc làm trong cơ quan chuyên môn thuộc UBND cấp huyện”, mã số: ĐT04/11, H. (2016) 47, 64.